2020
DOI: 10.3390/s20041052
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-Based Pulse Wave Sensor Utilizing a Piezoresistive Cantilever

Abstract: This paper reports on a microelectromechanical systems (MEMS)-based sensor for pulse wave measurement. The sensor consists of an air chamber with a thin membrane and a 300-nm thick piezoresistive cantilever placed inside the chamber. When the membrane of the chamber is in contact with the skin above a vessel of a subject, the pulse wave of the subject causes the membrane to deform, leading to a change in the chamber pressure. This pressure change results in bending of the cantilever and change in the resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…The authors are aware that there exist many different sensor technologies to measure the human pulse wave, ranging from optic 57 , 58 over ultrasonic 59 to force 20 , 54 , 55 , 60 65 sensing approaches. The force-sensing approaches make use of piezoresistive 60 , 61 , piezoelectric 54 , 55 or triboelectric 62 effects, or of capacitive changes 20 , 63 65 . Many of those devices are impressive with respect to their high sensitivity and ultrafast response time; for instance, Yao et al recently reported a piezoresistive sensor with an impressive sensitivity >10 7 Ω kPa −1 and a fast response time of 1.6 ms 60 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors are aware that there exist many different sensor technologies to measure the human pulse wave, ranging from optic 57 , 58 over ultrasonic 59 to force 20 , 54 , 55 , 60 65 sensing approaches. The force-sensing approaches make use of piezoresistive 60 , 61 , piezoelectric 54 , 55 or triboelectric 62 effects, or of capacitive changes 20 , 63 65 . Many of those devices are impressive with respect to their high sensitivity and ultrafast response time; for instance, Yao et al recently reported a piezoresistive sensor with an impressive sensitivity >10 7 Ω kPa −1 and a fast response time of 1.6 ms 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study has been carried out for designing a pulse wave measurement method using a MEMS cantilever based sensor [147]. The design has a thin piezoresistive cantilever of a thickness of 300-nm as a membrane inside the air chamber of sensors.…”
Section: Pulse Oximetermentioning
confidence: 99%
“…The sponge pad was used to prevent the air chamber from remaining collapsed due to the sticking of the film to the tape. Finally, the substrate on which the cantilever chip was mounted was attached to the back side of the tape with the To calibrate the cantilever, we applied differential pressure in the range of ±3 Pa to the cantilever and measured the fractional resistance change of the cantilever using a setup described in previous papers [13,14]. The calibration results in Figure 2c clearly show that the fractional resistance change of the cantilever ∆R/R is proportional to the applied differential pressure ∆P.…”
Section: Sensor Devicementioning
confidence: 99%
“…In this study, we used a 200-nm-thick piezoresistive cantilever [ 13 , 14 , 15 , 16 ] as the pressure sensing element. Figure 2 a shows a photograph of the fabricated cantilever and its design parameters.…”
Section: Sensor Fabricationmentioning
confidence: 99%